Índices de competitividad: Análisis de resultados para Colombia 2015-2016 (2016)
This article presents a first analysis of the measures results of Colombia competitiveness in 2015-2016 from a perspective of territorial development. It considered measures of the best-known indexes: The Global Competitiveness Report, Doing Business, and The IMD World Competitiveness Yearbook. The results exhibit a stable macroeconomic and financial level, and uncertainty panorama in institutional and territorial levels.